International conference devoted to 100th anniversary of V.M. Nadelyayev - Mizhit, Lyudmila S. (The New Research of Tuva, 2012)
Article reviews the International Scientific Conference "Turkic and Mongol peoples of Central Asia: language, ethnic history and folklore”, devoted to 100th anniversary of V.M. Nadelyayev. It was held on May 20-23, 2012 In Kyzyl.
Keywords: V.Nadelyayev; conference-2012; jubilee; review; turkology; linguistics; TIGI